Mechanism of bacteria adhesion on nanofilled tooth coloured restorative materials. - Dasmawati, Mohamad (Universiti Sains Malaysia, 2018)
Accumulation of microorganisms on the tooth surfaces has always lead to dental caries. The accumulation does not limit to tooth surfaces only but also to other surfaces that exist in the oral environment, commonly dental restorative materials. The adhesions of the microbial cells to the surface texture play a major significant in the accumulation of bacteria on intraoral solid surfaces. However, information on the mechanism and the force of adhesion on different substrate specifically in nanofilled tooth coloured dental materials are scarcely available. Furthermore, there are studies reported on the role of fluoride and their uneffectiveness in combating bacteria at early periods of adhesion (Carlen et al, 2001, Montanaro et al. 2004, Mohamad et al, 2007, Auschill et al, 2002). In previous work (Moharnad et al, 2007). it was found that the biofllm thickness was higher in the glass-ionomer cement (GIG) compared to the resin composite after 8 and 24 hrs. Studies of biofilm usually evaluated by confocal laser scanning microscopy (CLSM) but limited to thickness and topography of the bacteria only, but no quantity measurement betl.veen the bacterial eel! and the substrate. Recently, Oh et al 2009 has reported effects of substrates on biofilm formation observed by atomic force microscopy (AFM) and successfully obtained the force of adhesion. Therefore, within !his study, AFM will be utilized to evaluate the force of adhesion of bacterial. In generaL the objective of this study is to investigate on the effect of polished nanofilled GIG and resin Project Leader Member composite on the bacterial accumulation. In particular, the substrate morphological variation. force of adhesion and biofilm thickness will be evaluated. Analysis of gene expressions will also be evaluated by Real-time PCR This study is importance in understanding the mechanism which potentia!fy can be used for prevention of bacterial accumulation and thus reducing the secondary caries.